Pemanfaatan Mesin Pengayak dan Pengaduk Bahan Pembuatan Baglog Jamur di Desa Sidorejo Kecamatan Purwoharjo - Akhmad Afandi; Anggra Fiveriati; Anis Sufah Prastujati; Kuni Nadliroh (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
Banyuwangi is one of the regencies that has many small and medium businesses, one of which is oyster mushroom cultivation, precisely in Sidorejo Village, Purwoharjo District. Oyster mushroom cultivation is chosen by the community because it does not require a lot of capital and is easy to maintain. In the process of making baglog of oyster mushrooms, the most important thing is the process of sifting sawdust and stirring the mixture of ingredients for making baglog of mushrooms because it greatly affects the growth of mycelia unevenly. In general, partners in the process of making mushroom baglogs still use a manual system so that it is less efficient, especially in the process of sieving sawdust and mixing materials, so it requires an appropriate machine. In this service activity, the team provided a sieving machine and a mixer for a mushroom baglog mixture with a motor power of 1 PK, dimensions of 100cmx60cmx120cm, and a capacity of 100 kg/hour to speed up production. In addition, this program can help partners to better understand materials for making baglogs, the process of using machines, and maintenance after using machines effectively.